Relationship of Allergy with Asthma: There Are More Than the Allergy “Eggs” in the Asthma “Basket” - Guibas, George V.; Mathioudakis, Alexander G.; Tsoumani, Marina; Tsabouri, Sophia (Frontiers in Pediatrics, 2017)
Asthma and allergy share a similar and very close course, especially through childhood. Considerable research effort has been put in untangling these associations, however, it is now becoming obvious that this is an exceedingly difficult task. In fact, each research breakthrough further perplexes this picture, as we are steadily moving towards the era of personalized medicine and we begin to appreciate that what we thought to be a single disease, asthma, is in fact an accumulation of distinct entities. In the context of this ‘syndrome’ which is characterized by several, as of yet poorly defined endotypes and phenotypes, the question of the link of ‘asthma’ with allergy probably becomes non-relevant. In this review we will revisit this question while putting the emphasis on the multifaceted nature of asthma.